The Use of the Jigsaw Cooperative Learning Model as an Effort to Improve the Writing Skills of Knowledge Book Review for Class IX A Students of SMP Negeri 1 Padamara Odd Semester Academic Year 2018/2019 - Untung Pujiarto (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe the skills of writing a book review of knowledge based on the completeness and accuracy of the review element, the language used, the use of spelling, and punctuation. for IXA grade students of SMP Negeri 1 Padamara odd semester 2018/2019 using the jigsaw type cooperative learning model .. The approach used in this study is a qualitative research approach with a class action research design. This research was designed through classroom action research conducted in the form of an action cycle. This research was conducted in September 2018 until December 2018 in Class IXA of SMP Negeri 1 Padamara. Research data obtained from interactions between teacher and student, student and student and student teacher during the learning process. Data collection activities carried out by the method of observation, interviews, and documentation. Data analysis was performed with flow analysis which included (1) data reduction (2) data presentation, (3) drawing conclusions / verification, (4) data reflection, and (5) reflection of research findings. Research results both in terms of process and results. Writing learning can be concluded that the type of jigsaw cooperative learning model can improve the writing skills of knowledge book review in learning writing in class IXA SMP Negeri 1 Padamara odd semester of the 2018/2019 academic year. Keyword: Review writing skills, jigsaw type Abstrak Penelitian ini bertujuan untuk mendeskripsikan keterampilan menulis resensi buku pengetahuan berdasarkan kelengkapan dan ketepatan unsur resensi, bahasa yang digunakan, penggunaan ejaan, dan tanda baca. bagi siswa kelas IXA SMP Negeri 1 Padamara semester gasal tahun pelajaran 2018/2019 dengan menggunakan model pembelajaran kooperatif tipe jigsaw. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan penelitian kualitatif dengan rancangan penelitian tindakan kelas. Penelitian ini dirancang melalui penelitian tindakan kelas yang dilaksanakan dalam bentuk siklus tindakan. Penelitian ini dilaksanakan pada September 2018 sampai dengan Desember 2018 di Kelas IXA SMP Negeri 1 Padamara. Data penelitian diperoleh dari interaksi antara guru dan siswa, siswa dengan siswa dan siswa guru selama pembelajaran berlangsung. Kegiatan pengumpulan data dilakukan dengan metode pengamatan, wawancara, dan dokumentasi. Analisis data dilakukan dengan analisis mengalir yang mencakup (1) reduksi data (2) sajian data, (3) penarikan simpulan/ verifikasi, (4) refleksi data, dan (5) refleksi temuan penelitian. Hasil penelitian baik dari segi proses maupun hasil. Pembelajaran menulis tersebut dapat disimpulkan bahwa model pembelajaran kooperatif tipe jigsaw dapat meningkatkan keterampilan menulis resensi buku pengetahuan dalam pembelajaran menulis di kelas IXA SMP Negeri 1 Padamara semester gasal tahun pelajaran 2018/2019. Kata Kunci: Keterampilan menulis resensi, tipe jigsaw